ASUHAN KEBIDANAN KOMPREHENSIF PADA NY.P UMUR 39 TAHUN G5P3A1 DENGAN RESIKO TINGGI UMUR DAN GRANDE MULTIPARA DI PUSKESMAS BUMIAYU KABUPATEN BREBES - Zaitun Na’im; Endang Susilowati (Pusat Riset dan Inovasi Nasional, 2023)
Maternal mortality is a global health problem. The highest maternal mortality rate in central Java is Brebes regency. The Bumiayu health center contributes to the maternal mortality rate in Brebes district with 3 deaths in 2021. The purpose of this study was to be able to carry out Comprehensive Midwifery Care in Mrs.P aged 39 years G5P3A1 with Resti Age and Grande Multipara in Bumiayu health center with Varney and SOAP's seven-step midwifery management. The research method used is qualitative descriptive research with a case study approach. The case study conducted in the form of comprehensive widwifery care that examines woman during pregnancy, maternity, newborns, puerperium to Family Planning with seven-step languish management Varney and SOAP. The results of comprehensive widwifery care in Mrs.P, namely in pregnancy, preeclampsia was found Labor giving birth of casarean section and the newborns was normal. In the neonate found jaundice and then proper management was carried out so that the problem was resolved. During the Puerperium period, signs of Surgical Wound Infection were found and then collaborated with dr. Sp.OG so that the problem is resolved by Mom using KB MOW. Based on this care, it was concluded that the care provided had been carried out in accordance with midewifery service standards and the problems found can be resolved.